AAOM Clinical Practice Statement: Subject: Medical History - Miller, Craig, DMD, MS (Oral surgery, oral medicine, oral pathology and oral radiology, 2016)
Purpose The AAOM affirms that understanding the medical health of dental patients is important for proper dental care and the overall health of the patient. Methods This statement is based on a review of the current dental and medical literature related to the importance of a current medical history. A MEDLINE search was conducted using the terms “medical history,” “dentistry,” and “dental practice.” Expert opinions and best current practices were relied upon when clinical evidence was not available.